Video system for determining the number of people - Дзелендзяк, Уляна; Нікульшин, Данило (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2025)
The article investigates the effectiveness of using a video system to detect and track the movements of living objects, particularly people. A model for counting the number of people in a frame using the Arduino ESP_Camera hardware module and Python software has been developed. NumPy and OpenCV libraries have been used to process the video stream, which provide detection and tracking of movements in real time. The experimental results confirm that the system is able to accurately record the movements of people even in the presence of several moving objects, which indicates its practical effectiveness in real conditions. The proposed approach provides high accuracy in detecting movements in real-time video streams, which makes it promising for further application in the field of automated video surveillance.